2009
DOI: 10.1227/01.neu.0000338256.87936.7c
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation After Gamma Knife Radiosurgery for Vestibular Schwannomas Presenting With High-Level Hearing

Abstract: This study shows that the probability of preserving functional hearing in the long term after GKS for patients presenting with unilateral vestibular schwannomas is very high. The positive predictive factors appear to be young age, an initial symptom other than hearing decrease, and a low dose to the cochlea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 30 publications
3
119
1
2
Order By: Relevance
“…Of these, 16 retained serviceable hearing (84.2%), and 10 of the 16 (62.5%) retained GR Class I function. Tamura et al, 50 however, who reported on a larger sample size with a longer follow-up duration, noted that 50% of their patients retained GR Class I three years after radiosurgery and 78.4% retained serviceable hearing. As stated above, we cannot exclude the possibility that further hearing impairment will not occur during the ongoing follow-up.…”
Section: Hearing Function After Gksmentioning
confidence: 94%
See 2 more Smart Citations
“…Of these, 16 retained serviceable hearing (84.2%), and 10 of the 16 (62.5%) retained GR Class I function. Tamura et al, 50 however, who reported on a larger sample size with a longer follow-up duration, noted that 50% of their patients retained GR Class I three years after radiosurgery and 78.4% retained serviceable hearing. As stated above, we cannot exclude the possibility that further hearing impairment will not occur during the ongoing follow-up.…”
Section: Hearing Function After Gksmentioning
confidence: 94%
“…Our data also appear to be in line with the literature. 50 Crude rates of hearing preservation must be weighted with the time course of hearing in the long term. Hearing impairment usually occurs gradually over 6-24 months.…”
Section: Hearing Function After Gksmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also mentioned that patients who were not treated using gamma knife radiosurgery lost an average of 9-39 dB compared with an average loss of 2 dB at 3 years following radiosurgery, which corresponds with a preservation of hearing functionality of 60-75%. Tamura et al (Tamura et al, 2009) reported a 78.4% hearing preservation rate in Gardner-Robertson Class 1 patients. The probability of preserving functional hearing was higher in patients who had initial symptoms that were other than a decrease in hearing, in patients who were younger than 50 years, and in those patients whose cochlea received a dose of less than 4 Gy during treatment.…”
Section: Hearing Preservationmentioning
confidence: 96%
“…The probability of preserving functional hearing was higher in patients who had initial symptoms that were other than a decrease in hearing, in patients who were younger than 50 years, and in those patients whose cochlea received a dose of less than 4 Gy during treatment. (Tamura, et al, 2009). …”
Section: Hearing Preservationmentioning
confidence: 99%